Rasio Neutrofil Limfosit dan Kadar D-Dimer berdasarkan Derajat Keparahan Pasien COVID-19 di Rumah Sakit Semen Padang : Studi Kasus Kontrol - Besri, Hanifa Zahra; Efrida, Efrida; Jurnalis, Yusri Dianne; Putra, Andani Eka; Fitrina, Dewi Wahyu; Husni, Husni (UI Scholars Hub, 2023)
Introduction. Coronavirus Disease 2019 (COVID-19) is caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) which in 2020 was declared a global pandemic. In the management of COVID-19, patients are classified according to the severity. Identifying prognostic factors at an early stage helps assess severity risks. Abnormal hematological parameters were present in COVID-19 patients such as the elevation of neutrophil lymphocyte ratio (NLR) and D-dimer patients. This study aimed to determine the NLR and D-dimer levels based on the severity of COVID-19 patients. Methods. This study was an observational analytical study that used a case-control approach using 100 medical records of COVID-19 patients who were treated at Semen Padang Hospital in 2021. Consecutive sampling was used in this study. ANOVA test and the Kruskal-Wallis test were used for bivariate analysis. The results were considered significant if the p-value <0.05. Results. Characteristics of patients treated for COVID-19 were: 51% male and 49% female, mean age 57.79 (SD 13.5) years. NLR values based on the severity (mild, moderate, severe, and critical) were 3.12 (SD 2.04), 3.51 (SD 2.87), 6.89 (SD 3.6), 12.57 (SD 10.34) respectively; p<0.05. The median value of D-dimer (ng/mL) based on the severity (mild, moderate, severe, and critical) were 444, 791, 1,610, 2,135; p<0.05. The results of this study showed that there were significant differences in the NLR values and D-dimer levels based on severity. Conclusion. RNL value and D-dimer levels increase the most in the critical degree group and shows a significant relationship in COVID-19 patients.